A tale of two gyres: Contrasting distributions of dissolved cobalt and iron in the Atlantic Ocean during an Atlantic Meridional Transect (AMT-19). (November 2017) - Shelley, Rachel U.; Wyatt, Neil J.; Tarran, Glenn A.; Rees, Andrew P.; Worsfold, Paul J.; Lohan, Maeve C.
Highlights: Dissolved cobalt and iron have contrasting distributions in the upper 150 m of the North and South Atlantic gyres. Atmospheric deposition is not a major source of cobalt. The extremely low concentrations of dissolved cobalt in the North Atlantic gyre are driven by biological uptake. Abstract: Cobalt (Co) and iron (Fe) are essential for phytoplankton nutrition, and as such constitute a vital link in the marine biological carbon pump. Atmospheric deposition is an important, and in some places the dominant, source of trace elements (TEs) to the global ocean. Dissolved cobalt (dCo) and iron (dFe) were determined along an Atlantic Meridional Transect ( AMT -19; Oct/Nov 2009) between 50°N and 40°S in the upper 150 m in order to investigate the behaviour and distribution of these two essential, bioactive TEs. During AMT -19, large differences in the distributions of dCo and dFe were observed. In the North Atlantic gyre provinces, extremely low mixed layer dCo concentrations (23 ± 9 pM) were observed, which contrasts with the relatively high mixed layer dFe concentrations (up to 1.0 nM) coincident with the band of highest atmospheric deposition (∼5–30°N). In the South Atlantic gyre, the opposite trend was observed, with relatively high dCo (55 ± 18 pM) observed throughout the water column, but low dFe concentrations (0.29 ± 0.08 nM). Given that annual dust supply is an order of magnitude greater in the North than the South Atlantic, the dCo distribution was somewhat unexpected. However, the distribution of dCo shows similarities with the distribution of phosphate (PO4 3 − ) in the euphotic zone of the Atlantic Ocean, where the North Atlantic gyre is characterised by chronically low PO4, and higher concentrations are observed in the South Atlantic gyre (Mather et al., 2008), suggesting the potential for a similar biological control of dCo distributions. Inverse correlations between dCo and Prochlorococcus abundance in the North Atlantic gyre provinces, combined with extremely low dCo where nitrogen fixation rates were highest (∼20–28°N), suggests the dominance of biological controls on dCo distributions. The contrasting dCo and dFe distributions in the North and South Atlantic gyres provides insights into the differences between the dominant controls on the distribution of these two bioactive trace metals in the central Atlantic Ocean.